The Construction of Islamic Boarding School Education Ethics in Shaping the Character of Students: An Analysis of Discipline Policy in Islamic Boarding Schools - Isrun Abdurahman; Rizaldy Alpiansyah; Irfan Alkhotiri (Bahrul Ilmi : Journal of Islamic Religious Education, 2026)
This study aims to analyze the construction of pesantren education ethics in shaping the character of students through the policy of discipline at the Minhajul Haq Purwakarta Islamic Boarding School. A qualitative approach with a document analysis method was used to review the Santri Handbook as a primary data source. The results of the study show that the pesantren education system integrates three main pillars: strengthening faith and worship according to the manhaj of Ahlus Sunnah wal Jama'ah, mastery of active Arabic, and the formation of noble morals through the qudwah hasanah method. The reward and punishment mechanism is implemented through a comprehensive point credit system with 142 types of violations categorized based on the level of violation and accompanied by progressive sanctions. The policy of discipline reflects the construction of ethics that is holistic-integrative, combining aspects of worship, social ethics, administration, and mastery of Islamic competence. The implications of this study confirm that modern Islamic boarding schools maintain traditional values while adopting an international standard quality management system.